2022
DOI: 10.1007/s41064-022-00211-1
|View full text |Cite
|
Sign up to set email alerts
|

Developing and Evaluating Simplified Tools for Image Processing in a Problem-Based Learning Environment for Earth Observation

Abstract: Earth observation is an interdisciplinary field of application. This makes it ideal for supporting natural science education in schools. Understanding satellite data can enable students to see more than just “beautiful images”. They can gain insights into an exciting field of application of many natural- and computer science fundamentals. In recent years, interactive lessons have been produced by our working group. They address the prospects and challenges connected with the teaching of earth observation topic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Nevertheless, there is more to be done in the future, for CCSE or STEM education to capitalize on EO. In [16,17], authors have concluded that one of the largest concerns for the applicability of EO in schools is the content and how the materials can be adapted to the school curricula. Given that teachers are regarding EO as highly specialized and of a technical nature [18] and feel like they are stepping into uncharted territory, paying extra attention to how coherently the pedagogical content is presented should be regarded as a top priority.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nevertheless, there is more to be done in the future, for CCSE or STEM education to capitalize on EO. In [16,17], authors have concluded that one of the largest concerns for the applicability of EO in schools is the content and how the materials can be adapted to the school curricula. Given that teachers are regarding EO as highly specialized and of a technical nature [18] and feel like they are stepping into uncharted territory, paying extra attention to how coherently the pedagogical content is presented should be regarded as a top priority.…”
Section: Discussionmentioning
confidence: 99%
“…They enable non-expert users to explore and analyze different satellite images, apply various visualization and analysis tools, create custom image composites, and thus unlock the power of EO towards a greater environmental understanding. Such tools could potentially help overcome past hardware, support, or training necessities and thus encourage teachers to incorporate EO in their teaching if appropriate learning materials are made available [17].…”
Section: Eo Tools and Resourcesmentioning
confidence: 99%
See 2 more Smart Citations